ANALISIS PEMASARAN KOPI BUBUK MEREK SILVIA DI KECAMATAN BANGKINANG KOTA KABUPATEN KAMPAR - Hafiz Fauzan Azim; Ermi Tety; Evy Maharani (UIR Press, 2016)
Indonesia's population consume coffee as much as 0.98 kg/capita/year, coffee production any years necessary to review the Interior consumption ranged between 280,000 tons of coffee. Marketing strategy brand Silvia coffee powder can be known with how seeing funnel marketing, marketing efficiency, and marketing margins. The method is a method carried case studies. Ground coffee brand marketing Silvia there are two channels, direct marketing as much as 25.44% and indirect marketing as much as 74.56%. Efficiency direct marketing 0.52% margin Rp.0, indirect Marketing 0.60% margin Rp. 10,000.00. Product Strategy with attention to price, attributes, promotion and distribution. Product development is done with improvement production period, sustainability product and marketing accentuate attributes.